Advancement in Technology and the Long-Term Need for Energy (International Journal of Innovative Research in Computer Science & Technology, 2020)
This study examines how to include  technology advancement into energy-economy models  and how that affects long-term energy demand  predictions. The models range from an exogenous yearly  change in energy efficiency to an endogenous explanation  of energy technology innovation. Technological  advancement is frequently cited as the primary factor to  the differences in energy demand forecasts from various  models. Endogenous growth and industrial organization  theories have significant implications for efforts to  endogamies technical innovation and the diffusion of new  energy technologies. The article surveys several  theoretical and empirical theories of technological  development. This study compares two different models  of household energy consumption in Denmark. Two  macro econometric models, one for Denmark and the  other for the US, are compared. The two models' energy  demand projections vary, and it's up to us to prove that  the assumptions about technological development are the  cause. The forecast relies on assumptions regarding  energy efficiency improvements in older models. Vintage  modelling is less essential for long-term forecasts. Long term vintage modelling has a constraint that explains  some of the differences in predictions between the two  kinds of models. The current electric appliance model  does not properly represent the new energy-consuming  equipment that will be available in the future. This  category has to be modelled more thoroughly for long term predictions.
Keywords: Energy Demand; Energy-Economy Modelling; Exogenous; Innovation; Technological Development